Contribution of Darul Musannefin: history of Islam in Europe - Islam, Arshad (2014)
The First War of Independence (1857) was a key turning point in the colonial history of the Indian Subcontinent and marked a profound change in the life and governance of India. Following the violent suppression of the revolution, India was incorporated directly into the British Empire, introducing a secular colonial administration that marginalised the role of religion in Indian affairs. The whole of India suffered in the backlash, but the consequences were most devastating for the Muslims, the traditional rulers of northern India. It also accelerated the global campaign of the European colonialists to deny and destroy the contribution of Islamic civilization to the world. At this juncture, a cadre of remarkable Islamic scholars arose in India who attempted to preserve the Islamic heritage of India and to instil pride among Muslims in their faith, including Allama Shibli Nu’mani (1857-1914), who founded in 1914 the world famous Islamic institute Darul Musannefin (Shibli Academy) in his home town of Azamgarh. From its inception the institute was research-oriented, specializing in research on Islamic learning, medieval Indian history and oriental studies. While the association of Shibli, famous throughout the Muslim world for his magnum opus Al-Faruq, ensured the reputation of the institution, it made significant efforts in its own right by pioneering important works in the area of the history of Islam. As with contemporary reformers throughout the Muslim world, Shibli’s fundamental aim was to enable Muslim scientific and technical development within an Islamic framework, preventing the incursions of colonialism and secularism in the ideology of the Muslim world. Darul Musannefin continued Shibli’s mission of propagating books in Urdu that armed Indian Muslims against the ideological onslaught of the colonialists, with over 250 serious and scholarly publications and the journal Ma’arif, continuously issued since 1916, many of which focused on Muslim encounters with Europe and the intellectual contributions of Islamic civilization to the West,including Tarikh Daulat-i-Usmania (History of the Ottoman State) by Mohammad Uzair, Tarikh Saqlia (History of Muslim Rule in Sicily) and Tarikh Andlus (History of Muslim Spain) by Riyasat Ali Nadwi. This article enumerates and analyses the aims and objectives of its foundation and contribution in preserving the Islamic legacy and highlights the role of Muslim scholars in bringing into light to the Muslims’ achievements in the propagation and preserving the Islamic heritage in different parts of the world.